2012
DOI: 10.1111/j.1469-8749.2012.04336.x
|View full text |Cite
|
Sign up to set email alerts
|

Description of children with cerebral palsy: steps for the future

Abstract: This commentary is on the original article by Hidecker et al. on pages 737-742 of this issue.Describing children with cerebral palsy (CP) has long been a challenge for both clinicians and researchers, from the neurological (spastic, dyskinetic, ataxic) to the topographical subtypes (unilateral or bilateral, upper and ⁄ or lower limbs), and to the description of the accompanying impairments. 1 More recently, several ordinal scales have been proposed related to the activity limitations of children with CP based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
(5 reference statements)
1
0
0
Order By: Relevance
“…As was also demonstrated by similar studies [6][7]28], the study results indicated that there was a moderate to strong correlation between the Mini-MACS and GMFCS with the parent-and therapist-reported Mini-MACS scores. This slightly high correlation result, which most probably derives from the fact that children belonged to different types of CP [29], confirms and underlines the different construct that these two classification systems are built on and provide, fine versus gross motor function [6].…”
Section: Discussionsupporting
confidence: 56%
“…As was also demonstrated by similar studies [6][7]28], the study results indicated that there was a moderate to strong correlation between the Mini-MACS and GMFCS with the parent-and therapist-reported Mini-MACS scores. This slightly high correlation result, which most probably derives from the fact that children belonged to different types of CP [29], confirms and underlines the different construct that these two classification systems are built on and provide, fine versus gross motor function [6].…”
Section: Discussionsupporting
confidence: 56%